The delays in intestinal motility and neutrophil infiltration following burn injury in rats involve endogenous endothelins - (:unkn) unknown (ELSEVIER SCI LTD, 2000)
This study was carried out to investigate the role of endogenous endothelins in intestinal motility following burn injury by using a nonselective endothelin-1 (ET-1) antagonist and to evaluate the ET-1-mediated reactive oxygen metabolite formation and neutrophil infiltration following burn injury. In 2 h and 3 day postburn groups, transit indices were significantly decreased as compared to corresponding sham groups. Transit index was not significantly changed by PD156252 pretreatment in the 2 h postburn group, whereas the delay in transit was abolished in the ET-antagonist treated 3 day postburn group. In the 2 h postburn group, tissue-associated myeloperoxidase (MPO) activity value was found to be increased compared to corresponding sham group, while PD156252 pretreatment partially reversed this effect. Although MPO activity levels were not significantly different between 3 day postburn and corresponding sham groups, MPO levels showed a significant increase in ET antagonist-treated group as compared to the corresponding burn group. In the early phase of the burn, there was no significant difference in protein oxidation levels among the groups. In the 3 day postburn group, protein oxidation levels in ET-antagonist-treated group showed an increase compared to its corresponding burn group. In conclusion, the results demonstrate that endogenous endothelins have an important role in the systemic response to burn injury, as observed by a delay in intestinal motility and an infiltration of neutrophils. Although the results of the animal studies are not readily applicable to burned patients, the present study may suggest that the burned patient's condition should be carefully evaluated to secure a proper and early enteral feeding. (C) 2000 Elsevier Science Ltd and ISBI. All rights reserved.
Keywords: burns; oxidant toxicity; adhesion molecules; white cells; HUMAN POLYMORPHONUCLEAR LEUKOCYTES; ISCHEMIA-REPERFUSION INJURY; GUINEA-PIG ILEUM; THERMAL-INJURY; BACTERIAL TRANSLOCATION; RECEPTORS